Os múltiplos olhares sobre a educação ambiental em Januária - MG - Carvalho, Maria Veronica Fernandes de (2003)
The idea to distinguish education in this text was because its importance at the world setting, being everybody worried about the Earth Planet survival. We think the man can be changed just by Education and so, itis necessary to spread the obligation of the Man in front of the Nature, so soon as the first years at school, to avoid that, later, half measures will be done in a desesperate way. Knowing, early, the nature world and its value to the preservation of so many species, mainly the human one, all the respect will be dedicated to its conservation. Researchs have been done with the objective to know, with precision, the knowledge of the envolved persons, about environment, firstly when we are workingl with people who deal with Education. We notice, this way, that there are many things to do with the environment if we desire to change the sad present days, building a new way to have new manners in face of these ex.treme important facts. The best way to go out of these circunstances is to be supported on the holistic philosophy principles that doesn t loose itself in parts and guide ourselves to think about a general, participative and obligated way on a reality that lelongs to everybody.